Circulating MicroRNA Responses to Postprandial Lipemia with or without Prior Exercise - Springer, Catherine B.; Sapp, Ryan M.; Evans, William S.; Hagberg, James M.; Prior, Steven J. (International Journal of Sports Medicine, 2021)
Repeated exposure to a high-fat meal triggers inflammation and oxidative stress, contributing to the onset of cardiometabolic diseases. Regular exercise prevents cardiometabolic diseases and a prior bout of acute endurance exercise can counteract the detrimental cardiovascular effects of a subsequent high-fat meal. Circulating microRNAs (ci-miRs) are potential mediators of these vascular effects through regulation of gene expression at the posttranscriptional level. Therefore, we investigated the expression of ci-miRs related to vascular function (miR-21, miR-92a, miR-126, miR-146a, miR-150, miR-155, miR-181b, miR-221, miR-222) in plasma from healthy, recreationally to highly active, Caucasian adult men after a high-fat meal with (EX) and without (CON) a preceding bout of cycling exercise. Ci-miR-155 was the only ci-miR for which there was a significant interaction effect of high-fat meal and exercise (p=0.050). Ci-miR-155 significantly increased in the CON group at two (p=0.007) and four hours (p=0.010) after the high-fat meal test, whereas it significantly increased in the EX group only four hours after the meal (p=0.0004). There were significant main effects of the high-fat meal on ci-miR-21 (p=0.01), ci-miR-126 (p=0.02), ci-miR-146a (p=0.02), ci-miR-181b (p=0.02), and ci-miR-221 (p=0.008). Collectively, our results suggest that prior exercise does not prevent high-fat meal-induced increases in vascular-related ci-miRs.
Keywords: microRNA; exercise; postprandial lipemia; vascular